Design Learning Mathematics Through Approach Constructivism on Comparative Material Worth it in Perspective Culture Making Dodol Jackfruit Typical Lombok - Destika Amriatul Aini; Aryanti Ramadhani; Atika Febri Nurcahyani; Zahratul Hayati; Supiarmo, M. Gunawan (Tinta Emas Publisher, 2025)
Mathematics has an important role in solving various problems in everyday life, including in the fields of commerce, measurement, and astronomy. One of the goals of learning mathematics is to train logical thinking and problem solving skills. However, students often experience difficulties with comparing materials, such US determine unit values, classifying types of comparisons, and compare fractions. This difficulty requires contextual and interesting learning strategies, such US ethnomathematics-based learning. Ethnomathematics integrates local culture into mathematics learning to make it more relevant and meaningful. This research highlights local Lombok culture, especially the process of making jackfruit dodol, as a context for learning value comparisons. The research uses a qualitative approach with a development studies type design research method. Research steps include studying the concept of value comparison, constructivism theory, and the relationship between local culture and mathematics. The learning design developed emphasizes the involvement of students as learning subjects (constructivist learning) to build understanding through direct experience. It is hoped that this ethnomathematics-based learning will not only improve students' understanding of mathematics but also introduce and preserve local culture.